2015
DOI: 10.1080/09613218.2015.1039284
|View full text |Cite
|
Sign up to set email alerts
|

Handover defects: comparison of construction and post-handover housing defects

Abstract: Although inspections occur during construction or at handover, customers do not normally participate. This situation creates a gap between quality perceived by contractors and customers. An analysis of 52,552 handover defects in 2,179 flats in Spain is presented which identified their nature, the building element and trade where these defects are located. These results are compared to previous studies that analyzed defects detected during the construction stage and those that remain after handing over the buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 22 publications
2
63
0
2
Order By: Relevance
“…The absence of a standard lexicon widens the gap between the customer and the developer and can further affect customer satisfaction (Sommerville, 2007). Forcada, et al (2016) found that even in cases where the same terminology was used when describing the nature of defects during the construction, handover and post-handover stages, the types of defects differ. Disputes can even arise between industry professionals, who do not always place the defects in the same classification (Georgiou, 2010).…”
Section: Building Quality Trust and Customer Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of a standard lexicon widens the gap between the customer and the developer and can further affect customer satisfaction (Sommerville, 2007). Forcada, et al (2016) found that even in cases where the same terminology was used when describing the nature of defects during the construction, handover and post-handover stages, the types of defects differ. Disputes can even arise between industry professionals, who do not always place the defects in the same classification (Georgiou, 2010).…”
Section: Building Quality Trust and Customer Satisfactionmentioning
confidence: 99%
“…Previous research has discussed inspection from a technical or legal perspective and has predominantly been based on inspection audits as the source of data on the occurrence and type of defects ( Johnsson and Meiling, 2009;Forcada, et al, 2016). Studies on building defects have mainly focused on the occurrence of defects (Forcada, et al, 2016;Sommerville, 2007;Atkinson, 1999), the relationship between defects and customer satisfaction (Auchterlounie, 2009;Milion, Alves and Paliari, 2017;Fauzi and Abidin, 2012), diagnosis of defects (Kangwa and Olubodun, 2006;Sui Pheng and Wee, 2001), or the cost and remediation of defects (Hopkin, et al, 2017). Though the human factor and effect on building quality has been recognised by Sunding and Ekholm (2014) and Forsythe (2015), the correlation between the inspection process, the inspector and the owner has not fully been examined from the perspective of the owner's knowledge base and pathways to trust especially within multidwelling housing.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, several defects in buildings have been identified. The defects include: fungi growth, discolouration, waterproofing system, cracks in walls, roof leakages, soil settlement, rainwater penetration, leakage problems, corrosion of steel structure, faulty communication appliance, faulty doors and windows, roof damages, mechanical and electrical system faults (Forcada et al, 2015;Olanrenwaju, 2012;Wahab and Hamid, 2011;Wong and Jan, 2003). However, Olarenwaju (2012) acknowledged that the degree of impact of defective facilities on users' is dependent on the users' requirements in terms of safety, security, convenience and comfort.…”
Section: Literature Review Defects In Building Facilitiesmentioning
confidence: 99%
“…Por su parte, Andrea Paladio dijo en su primer Libro de Arquitectura (capítulo 1): "se debe también atender a la calidad y bondad de los materiales, a fin de elegir los mejores; en esto, nos ayudará mucho la experiencia tomada de las obras construidas por otros, pues advertidos por ellas podremos determinar fácilmente lo que a nuestra necesidad más acomoda" (28). Como resumen global, podemos hacer la siguiente reflexión en relación al análisis efectuado y las casuísticas de otros estudios consultados: El sector de la construcción español es uno de los sectores económicos donde más problemas de producción y detección de incidencias post-entrega hay (29). Esta realidad señala una evidente insatisfacción del destinatario final, pero también muestra que existen ciertos aspectos constructivos que tendrían que ser mejorados.…”
Section: La Calidad De La Mano De Obra En Españaunclassified